A Semi‐Batch Flow System for the Production of 5‐Chloromethylfurfural. Issue 10 (2nd June 2021) - Smith, Bailey A.; Champagne, Pascale; Jessop, Philip G.
Abstract: The bioplatform molecule 5‐chloromethylfurfural (CMF) has potential as an intermediate or precursor in the preparation of useful products, such as bioderived fuels, chemicals and polymers. The replacement of the halogenated solvents and the use of a semi‐batch system have been investigated in the synthesis to reduce the human and environmental safety concerns associated with current CMF production methods. The new method gives a high yield of CMF from fructose without chlorinated solvents, and can be extended to the synthesis of CMF from other feedstocks such as sugars, cellulose, seaweed and sawdust. Abstract : Green conversion : If a semi‐batch flow system is used, then it is possible to convert sugars into 5‐chloromethylfurfural in good yields without the use of chlorinated solvents. The new method addresses environmental and safety concerns associated with DCE use and demonstrates the use of cellulose, seaweed and sawdust as the starting material.